NAVIGATING COMPLEXITY: THE MODERATING ROLE OF JOB COMPLEXITY IN ENHANCING NURSE PERFORMANCE THROUGH JOB RESOURCES AND ENGAGEMENT - Zubaidah Z; Irsan Tricahyadinata; Irwan Gani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
In the dynamic healthcare environment, nurse performance plays a pivotal role in ensuring high-quality service delivery. However, work pressure, administrative burdens, and rising public expectations pose significant challenges. This study investigated how job resources influence nurse performance, as mediated by work engagement and moderated by job complexity. Drawing on the Job Demands–Resources (JD-R) model, this study employed a quantitative, cross-sectional survey involving 174 nurses in private hospitals in East Kalimantan, Indonesia. Using partial least squares structural equation modelling (SEM-PLS), this study confirms that job resources significantly enhance both work engagement and performance, with engagement serving as a key mediator. Interestingly, job complexity did not significantly moderate the relationship between job resources, engagement, and performance. These findings suggest that supportive work environments remain critical, even in standardised healthcare settings, and that job complexity may not universally enhance motivational dynamics. This study contributes to the literature by extending the JD-R model to a developing country context and informing hospital HR policies on resource investment strategies.